Effects of Lending Relationship on the Interest Rates of Commercial Banks in Cameroon - Forgha, Njimanted Godfrey; Serge, Tameta; Aquilas, Nkwetta Ajong (Asian Journal of Economic Modelling, 2018)
Borrowing is the main stream through which small and medium size enterprises obtain funds for investment in Cameroon, and interest rate is a key determinant of how much funds these firms can acquire. It is against this backdrop that this study investigates the effects of lending relationship on the interest rate of commercial banks. Specifically, this study examines the effects of lending relationship factors like duration, pre-existence and trust and firm characteristics such as age, size, incorporation form and the gender of bank borrowers on the lending interest rates of commercial banks. A total of 119 questionnaires were administered to 9 commercial banks and their borrowers in Fako Division, South West Region of Cameroon and the ordered logistic regression method was employed as the analytical technique. Findings showed that trust in a relationship, preexisting relationship, firm size and incorporation form and gender of bank borrower significantly affect lending interest rate while duration of the relationship and firm age had insignificant effects. It was recommended that commercial banks should consider using relational social control measures.